Effect of a histidine-tryptophane-ketoglutarate solution on coagulation as measured by a thromboelastogram - Kabambi, Kasandji Freddy (Department of Anaesthesia, 2017)
Background: The Histidine-tryptophan-ketoglutarate (HTK) solution is cardioplegic solution that confers myocardial protection during periods of ischemia in heart surgery. It has the advantage of allowing a longer protection and it is especially the preferred cardioplegic solution in complex paediatric heart surgery like transposition of great vessels. This has also been used in organ transplant as a preservative solution. Recently concern has been raised over its safety because of the increased incidence of transplant failure due to thrombosis in individuals whose transplanted organ were preserved with HTK solution. The main purpose of this study was to establish whether the HTK solution in the dose and volume used for myocardial protection during paediatric heart surgical procedures increases the thrombotic risk of patients. Patient and methods: This study was an experimental study conducted at the coagulation laboratory of the department of anaesthesia of the University of Cape Town. The human research ethical committee of this university approved this study. Twenty healthy individual were recruited for this study and each one of them read and signed the consent form before being enrolled for the study. The exclusion criteria were any known coagulopathy, liver diseases, alcoholism, kidney disease and intake of any drugs known to impair the coagulation. Ten millilitre of blood was drawn from the volunteer at the coagulation laboratory. The blood was diluted with either HTK solution or St Thomas' cardioplegic solution at 9:1 ratio to mimic the hemodilution due to HTK solution in paediatric population. The effect on coagulation was assessed by means of thromboelastography run on the native blood and each dilution separately. Results: The difference in the magnitude of change from baseline in r-time between the HTK solution and Saint Thomas' solution (mean difference 0.49 min) (p 0.014) was statistically significant. There was no statistically significant change in MA between the HTK solution and St Thomas' solution (mean difference -2.13 mm) (p 0.165). Compared to native blood there were no significant change in r-time with the HTK solution (mean -0.215 min), the same with St Thomas' solution. Compared to native blood, there was significant change in maximum amplitude with the HTK solution (mean 1.38 mm) the same with St Thomas' solution (mean 3.51). Although the difference in the magnitude of in R time change between HTK solution and St Thomas' was statistically significant, it is clinically not relevant. The data did not show a trend that might become significant with large sample. All variables showed a slight tendency towards decreased coagulation in the diluted samples, but not of sufficient magnitude to be clinically important. Our goal was the use of a dilution that is clinically relevant in the context of paediatric cardiac surgery. Conclusion: The results of this study suggest the HTK solution at 10% dilution does not cause significant changes in coagulation parameters. In comparison to normal saline, there were a tendency toward hypocoagulation. More research in this field is needed to clarify the pathophysiologic pathways of thrombosis observed in these transplants.